2019
DOI: 10.3390/app9152962
|View full text |Cite
|
Sign up to set email alerts
|

“Texting & Driving” Detection Using Deep Convolutional Neural Networks

Abstract: The effects of distracted driving are one of the main causes of deaths and injuries on U.S. roads. According to the National Highway Traffic Safety Administration (NHTSA), among the different types of distractions, the use of cellphones is highly related to car accidents, commonly known as “texting and driving”, with around 481,000 drivers distracted by their cellphones while driving, about 3450 people killed and 391,000 injured in car accidents involving distracted drivers in 2016 alone. Therefore, in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Additionally, their results demonstrated that different conditions, such as recently having a heavy meal, could affect the measuremente [22]; a similar approach was explored by Kulkarni et al [23]. Finally, and related to the topic of ubiquitous approaches to detect unsafely behaviors, Celaya et al [24] presented a system that detects when a subject is texting and driving. The authors used a wide angle camera inside the vehicle to record and analyze the behavior of the driver, detecting the use of a cellphone while driving by means of a deep neuronal network, with an accuracy of 0.89.…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, their results demonstrated that different conditions, such as recently having a heavy meal, could affect the measuremente [22]; a similar approach was explored by Kulkarni et al [23]. Finally, and related to the topic of ubiquitous approaches to detect unsafely behaviors, Celaya et al [24] presented a system that detects when a subject is texting and driving. The authors used a wide angle camera inside the vehicle to record and analyze the behavior of the driver, detecting the use of a cellphone while driving by means of a deep neuronal network, with an accuracy of 0.89.…”
Section: Introductionmentioning
confidence: 92%
“…In the successive layers, these filters are progressively increasing, finally achieving improved accuracy and the false positive rate is lower. J. M. Celaya-Padilla et al [17] have presented a method which is adapted ubiquitously for the detection of drivers who are distracted by using their cellphones. For this research study, the authors have used a wide-angle camera mounted on a ceiling which is integrated with a deep learning CNN.…”
Section: Recent Literaturementioning
confidence: 99%
“…J. Celaya-Padilla et al [101] have proposed a novel ubiquitous oriented methodology to detect distracted drivers who are using cellphones. The authors have mounted a wideangle camera on the roof to compile a video of the driver and then each video is is split into 24 pictures.…”
Section: A Comparative Study Of Driver Distraction Detection Techniqmentioning
confidence: 99%